Exploring The Dynamics of Learning Orientation and Technology Integration in Shaping Organisational Behaviour – A Structural Analysis Through ISM and MICMAC (MSW Management Journal, 2026)
Purpose: Organisations require employees who excel in their roles and willingly engage in extra-role behaviours known as organisational citizenship behaviour (OCB). This study aims to identify and analyse the factors that influence OCB, directly or indirectly, and explore their contextual relationships. Additionally, it establishes a hierarchical framework to clarify the critical components of OCB.Methodology: The research uses the Interpretive Structural Modeling (ISM) approach to analyze the structural hierarchy and interconnections among variables such as OCB, innovative work behavior, task performance, job satisfaction, leadership style, emotional intelligence, learning orientation, and technology integration. A thorough review of existing literature and expert opinions forms the basis of the analysis. MICMAC (Cross-Impact Matrix Multiplication Applied to Classification) analysis is employed to categorize factors into autonomous, independent, dependent, and related groups based on their driving and dependent powers.Findings: The study constructs a structural model showing the relationships between the factors. Leadership style is identified as the most influential independent factor, positioned at the top of the hierarchy. In contrast, task performance, emotional intelligence, and learning orientation are placed at the bottom as dependent factors. These dependent variables reflect a subordinate role in influencing OCB. The findings emphasize the critical role of leadership style in shaping OCB.Implications: While previous research has explored individual factors associated with OCB, this study bridges a gap in the literature by demonstrating their interrelationships. The research underscores the importance of leadership style in driving OCB and related outcomes.Originality and Value: Unlike prior studies that relied on content analysis, quality management techniques, and the Analytical Hierarchical Process (AHP), this research employs the ISM-MICMAC technique, making it a novel approach to studying OCB and its influencing factors.